TINJAUAN YURIDIS KEPASTIAN HUKUM NOMINEE AGREEMENT KEPEMILIKAN SAHAM PERSEROAN TERBATAS - , Lucky Suryo W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed to: (1) find out the formation of nominee agreement prevalent used for limited liability share ownership in Indonesia. (2) find out the position of nominee agreement in Indonesia legal rules (3) find out a thorough overview of the responsibilities of Notary in case of nominee agreement. The research was a juridical normative research, namely research that explore legal issues in society with the approach of positive law and legal principles. As a normative research, the research is based on research by examining the secondary data field of the existing law as literature data using deductive reasoning and coherent criterion of validity. Based on the research, it can be concluded that